The development of Light-weight High Entropy Alloy (LWHEA) composites Al35Ti35Si(20-x) Be10Bx (x=1,2,3) wt.% prepared by powder metallurgy route - Dlamini, Sibongile Mabel (Vaal University of Technology, 2022)
High entropy alloys (HEAs) are novel alloys with five or more primary elements in an equiatomic or near-equiatomic proportionate ratio. The configuration entropy in HEAs tends to stabilize the development of solid solutions like body-centred-cubic (BCC), face-centred-cubic (FCC), and hexagonal-closed-pack (HCP). Compared to traditional alloys, the increased number of primary elements present in HEAs causes severe lattice distortion, resulting in higher mechanical properties. HEAs are seen as a radical transformation for the next generation of high-temperature alloys in extreme conditions like aircraft, cutting tools, and bearings. The main objective of this dissertation was to develop new types of Al35Ti35Si(20-x)Be10Bx (x=1,2,3 wt.%) lightweight high entropy alloys using mechanical alloying and Spark plasma sintering to understand better how microstructures evolve during sintering and secondary processing, as well as the mechanical properties that can be derived. The first part of the project involved subjecting the elemental powders (aluminium, titanium, silicon, beryllium and boron) chosen for this work to mechanical alloying for 45 hours. Subsequently, applying plasma sintering to produce all the three fully densified alloy composites: Al35Ti35Si19Be10B, Al35Ti35Si18Be10B2, and Al35Ti35Si17Be10B3 at 1000 ºC with densities 3.48, 3.40 and 3.51 gꞏcm-3, respectively. The sintered alloys showed the formation of BCC and FCC solid solutions as well as ordered solid solution phases such as Ti4Si8/ Ti16Si32, Al4Ti8O2, and B2N2, with a microhardness of 957, 989, and 1093 HV, respectively. The three developed alloys also showed remarkable corrosion resistance in a 3.5 wt.% NaCl solution. Tribological characteristics of the developed Al35Ti35Si(20-x)Be10Bx (x=1,2,3 wt.%) alloys were examined under dry sliding wear conditions with stainless steel as the static friction partner under a 10 N load and a sliding duration of 60 min. The results indicated that the increase of silicon in the alloy has an impact on the friction coefficient and wear rate. High-temperature oxidation test was also conducted for Al35Ti35Si19Be10B, Al35Ti35Si18Be10B2, and Al35Ti35Si17Be10B3 alloys at 700 and 900 ºC for 400 hours and 200 hours, respectively. These alloys showed good resistance to high-temperature oxidation at 900 ºC as compared to oxidation at 700 ºC. The resistance to oxidation was indicated by low weight gain and low rate constant.
M. Eng. (Department of Metallurgical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Light-weight High Entropy Alloy (LWHEA); High entropy alloys (HEAs); Body-centred-cubic (BCC); Face-centred-cubic (FCC); Hexagonal-closed-pack (HCP); Structural properties; High hardness/strength; Corrosion resistance; Wear Resistance; Strengthening Mechanisms; Effect of alloying elements; Dissertations, Academic -- South Africa.; Alloys.; Light metals -- Metallurgy.; Materials -- Mechanical properties.; Mechanical alloying.